Patients Awareness and Satisfaction in Government Hospital: A Study of Madina and Kahanaur CHCs in Rohtak District - Dr. Kavita A. Jain; Savita (International Journal of Engineering and Management Research, 2022)
The present research study has been conducted to gain knowledge about awareness level of patients and their satisfaction towards facilities and services provided in government hospitals. In order to achieve the objective of this research work, the researchers collected primary data from 100 respondent patients (50 from Madina and 50 from Kalanaur CHCs). In this connection, level of awareness and satisfaction level of patients have been measured with the help of Likert’s five point scale measurement. The obtained results of this study suggested that some efforts should be made by the CHCs’ staff to improve the satisfaction level of patients.